2017
DOI: 10.1016/j.pmatsci.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A review on the strain rate dependency of the dynamic viscoplastic response of FCC metals

Abstract: The response of structures and materials subject to impulsive loads remains a field of intense research. The dynamic loading and temperature increase affect the material's mechanical/failure response. For example, strains due to explosive blast will increase at rates from 102 to 104 s-1, leading to regimes of elastic/plastic wave propagation, plane stress and adiabatic deformations. Few constitutive models consider high strain rate effects, however some constitutive approaches that were developed and tested at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 145 publications
(285 reference statements)
1
41
0
Order By: Relevance
“…The proposed concept is quite different from the celebrated strength models introduced by Zerilli and Armstrong [18], Johnson and Cook [19], Follansbee and Kocks [20], Preston, Tonks and Wallace [21], among others [22]. The models are based on a salient assumption that the yield stress carries all H p results from slip events along many θ planes defined by two orthogonal unit vectors, n θ and s θ .…”
Section: Introductionmentioning
confidence: 98%
“…The proposed concept is quite different from the celebrated strength models introduced by Zerilli and Armstrong [18], Johnson and Cook [19], Follansbee and Kocks [20], Preston, Tonks and Wallace [21], among others [22]. The models are based on a salient assumption that the yield stress carries all H p results from slip events along many θ planes defined by two orthogonal unit vectors, n θ and s θ .…”
Section: Introductionmentioning
confidence: 98%
“…These are only few examples of an extensive literature. A detailed review of experimental testing and modelling for bcc metals can be found in [22,23] and more recently in [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Often, it is assumed 4 that the thermally activated dislocation mechanism operates at all strain rates, while others 5 have argued that both thermal activation and drag-controlled mechanisms coexist at high strain rates. A comprehensive review of the theoretical concepts and models is presented in refs 6,7 . In various constitutive descriptions, the effort is focused on connecting the material responses at high strain rates with the rapid increase of dislocation density and the development of fine dislocation structures.…”
Section: Introductionmentioning
confidence: 99%